Region based find and spray scheme for co-operative data communication in vehicular cyber-physical systems. Issue 3 (3rd July 2017) - Chinnasamy, Poongodi; J, Premalatha; K, Lalitha; D, Vijay Anand
Abstract: Smart transportation in Vehicular Cyber Physical Systems (VCPS) are addressing a range of problems including reducing traffic accidents, congestion, fuel consumption, time spent on traffic jams, and to improve transportation safety. Smart transportation VCPS is expected to contribute an important role in the design and development of intelligent transportation systems. Intermittently Connected Vehicular Networks (ICVNs) are a kind of intelligent transportation systems, where due to mobility of vehicles there may be disconnections among the source and destination vehicles. A multi-hop scenario is used here, where a stationary road side unit exchanges data packets with a destination outside its communication range, using passing-by vehicles as information carriers. In order to deal with these ICVNs, an efficient routing scheme is necessary to withstand the maximum delay. We propose a routing scheme, which makes use of the movement history among the regions for routing a message. The proposed scheme tries to use the single copy routing wherever possible and then do fuzzy controlled multiple replications. Results show that the proposed scheme outperforms existing methods in terms of packet delivery ratio, packet delay and protocol overhead.